Combination Treatment for Extensive Chromoblastomycosis: A Case Report - Dhan Keshar Khadka; Dipayan Pandey; Sudha Agrawal (Nepal Journal of Dermatology, Venereology & Leprology)
Chromoblastomycosis is a chronic and progressive recalcitrant fungal infection of the cutaneous and subcutaneous tissue caused by traumatic inoculation of a specific group of dematiacious fungi through skin. There are different treatment modalities for chromoblastomycosis (medical/surgical) having various efficacy. However, there is no treatment of choice for this disease. Though several therapeutic regimen has been proposed for almost 100 years, the disease may be recalcitrant and almost difficult to eradicate if diagnosed in later stage. Relapses are frequently reported. A combination of various treatment modalities is needed to achieve the best result.